Information security management handbook on CD-ROM - Krause, Micki; Tipton, Harold F. (Boca Raton, FL : Auerbach/CRC Press, 2008)
This CD-ROM contains an extra volume's worth of information that is not found anywhere else, including chapters from other security and networking books that have never appeared in the print editions
Title from cover page of book
System requirements: Pentium III processor or higher; 128MB RAM; 15MB available disk space; CD-ROM drive (4x) or higher or DVD-ROM drive; SVGA monitor at 800x600, 256 colors
Keywords: Data protection -- Handbooks, manuals, etc; Computer security -- Management -- Handbooks, manuals, etc; Data protection -- Handbooks, manuals, etc